2020
DOI: 10.1016/j.celrep.2020.108362
|View full text |Cite
|
Sign up to set email alerts
|

Prepronociceptin-Expressing Neurons in the Extended Amygdala Encode and Promote Rapid Arousal Responses to Motivationally Salient Stimuli

Abstract: SUMMARY Motivational states consist of cognitive, emotional, and physiological components controlled by multiple brain regions. An integral component of this neural circuitry is the bed nucleus of the stria terminalis (BNST). Here, we identify that neurons within BNST that express the gene prepronociceptin ( Pnoc BNST ) modulate rapid changes in physiological arousal that occur upon exposure to motivationally salient stimuli. Using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 78 publications
(122 reference statements)
3
52
0
Order By: Relevance
“…BNST vGLUT2 -PBN neurons are enriched in Adcyap1, which encodes the neuropeptide pituitary adenylate cyclase-activating peptide (PACAP), previously identified as a major regulator of stress responses in the BNST (30,31), including in contexts of addiction and posttraumatic stress disorder (32,33). Both BNST vGAT -PBN and BNST vGLUT2 -PBN neurons express calcitonin receptor (Calcr), recently associated with the regulation of feeding (34,35), and nociceptin (Pnoc), linked to motivated behaviors including feeding (24,(36)(37)(38). We further validated these RNA sequencing (RNA-seq) findings by performing fluorescent in situ hybridization experiments, which revealed coexpression of Tac2, Sstr3, and Calcr with vGAT and Adcyap1 with vGLUT2 neurons within the BNST ( fig.…”
Section: Anatomical and Molecular Characterization Of Opposing Bnst-pmentioning
confidence: 99%
“…BNST vGLUT2 -PBN neurons are enriched in Adcyap1, which encodes the neuropeptide pituitary adenylate cyclase-activating peptide (PACAP), previously identified as a major regulator of stress responses in the BNST (30,31), including in contexts of addiction and posttraumatic stress disorder (32,33). Both BNST vGAT -PBN and BNST vGLUT2 -PBN neurons express calcitonin receptor (Calcr), recently associated with the regulation of feeding (34,35), and nociceptin (Pnoc), linked to motivated behaviors including feeding (24,(36)(37)(38). We further validated these RNA sequencing (RNA-seq) findings by performing fluorescent in situ hybridization experiments, which revealed coexpression of Tac2, Sstr3, and Calcr with vGAT and Adcyap1 with vGLUT2 neurons within the BNST ( fig.…”
Section: Anatomical and Molecular Characterization Of Opposing Bnst-pmentioning
confidence: 99%
“…The MeA subnuclei are involved with the (1) interpretation of environmental cues of conspecific stimuli; (2) processing of multiple sensory information, including direct and indirect olfactory and vomeronasal inputs with social relevance; (3) cellular responses to neural gonadal steroid actions for neuroendocrine secretion; and (4) modulation of reproductive and other social behaviors in rodents (Newman, 1999;Meredith and Westberry, 2004;Choi et al, 2005;Pro-Sistiaga et al, 2007;Rasia-Filho et al, 2012a,b;Petrulis et al, 2017;Petrulis, 2020). Being part of an organized neural network that projects to the bed nucleus of the stria terminalis (see relevant data on arousal behavior in Rodriguez-Romaguera et al, 2020) and to various hypothalamic and brainstem nuclei, the CeA and MeA subnuclei also participate in social and defensive reactions against innate and learned threats with neuroendocrine, behavioral, and sympathetic/parasympathetic responses to fearful and stressful stimuli (Davis, 1992;LeDoux, 1992;Quirk et al, 1995;Dayas et al, 1999;Rasia-Filho et al, 2000, 2012bPetrovich et al, 2001;Marcuzzo et al, 2007;Neckel et al, 2012;Petrulis, 2020;Anilkumar et al, 2021). In humans, the extended amygdala responds to the emotional salience of positive and negative affect (Liberzon et al, 2003).…”
Section: The Amygdaloid Complex and "Cortical-like Structures" Advancing To The Allocortex And Neocortexmentioning
confidence: 99%
“…In our analysis, we used bulk sequencing data of cholangiocarcinoma patients in TCGA database to calculate the immune infiltration scores of different immune cell populations, and then we compared expression difference between groups, locating immune infiltration highly associated genes; we found PNOC was mainly expressed by infiltrated B cells, which was survival related, while LAIR2 was mainly expressed by Tregs and partial CD8+/GZMB+ T cells, indicating exhaustive immune status of T cells. Prepronociceptin (PNOC) was formerly reported to be a preprotein for a series of products, which act as pain regulators in signal transduction (38). Recent study showed PNOC is involved in long-term opioid response, alcoholic states, and inflammation process (39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%